Analisis Pengaruh Rasio Nilai Pasar, Solvabilitas Dan Profitabilitasterhadap Harga Saham Pada Perusahaan Yang Terdaftar Di Indeks Lq-45 Tahun 2013 - 2017 - Sitorus, Bode Verry Fair (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aims to help investors or prospective investors in making decisions in investing in the capital market by analyzing the influence of financial ratios, namely market value ratios, solvency and profitability that affect stock prices in companies that are consistently registered in the LQ-45 period 2013-2017 . The market value ratio used is Price to Earning Ratio (PER) and Price to Book Value (PBV), the solvency ratio used is Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER) while the profitability ratio used is Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM). This study uses a purposive sampling technique with a sample of 24 LQ45 issuers who meet the research criteria for the period 2013-2017 from 45 existing issuers. The results of this study that stock prices can be explained as much as 24.68% by Price to Book Value (PBV), Debt to Assets Ratio (DAR), Debt to Equity Ratio (DER), Return On Assets (ROA), Return On Equity ( ROE) and Net Profit Margin (NPM. Simultaneously all independent variables have an effect on stock prices while from the seven variables, only the Price to Book Value (PBV) variable has an effect on stock prices. Therefore investors or potential investors should pay attention to the Price ratio. to Book Value (PBV) as a reference in investing.